2015
DOI: 10.1016/j.bone.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dose and type of proton pump inhibitor use on risk of fractures and osteoporosis treatment in older Australian women: A prospective cohort study

Abstract: Please cite this article as: van der Hoorn Mariëlle M.C., Tett Susan E., de Vries Oscar J., Dobson Annette J., Peeters G.M.E.E. (Geeske), The effect of dose and type of proton pump inhibitor use on risk of fractures and osteoporosis treatment in older Australian women: a prospective cohort study, Bone (2015Bone ( ), doi: 10.1016Bone ( /j.bone.2015 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 44 publications
(67 reference statements)
3
40
0
1
Order By: Relevance
“…Potential risk factors for osteoporosis in this study were classic risk factors for osteoporosis such as age, sex, body weight, malnutrition (assessed using the Patient-Generated Subjective Global Assessment (PG-SGA) malnutrition screening tool recommended by the American Society of Parenteral and Enteral Nutrition (ASPEN)), physical inactivity (assessed using the PG-SGA activities and function evaluation), serum 25-hydroxyvitamin D deficiency, hypocalcemia, hyponatremia, hypogonadism (assessed using serum levels of estradiol, follicle stimulating hormone, luteinizing hormone, and testosterone), hyperparathyroidism, thyroid dysfunction, history of alcohol consumption (yes vs. no; self-reported current or prior alcohol consumption of any frequency or duration), history of cigarette smoking (yes vs. no; self-reported current or prior smoking of any frequency or duration), current use of selective serotonin reuptake inhibitors (SSRIs; yes vs. no), and current use of proton-pump inhibitors (PPIs; yes vs. no) (32-34). …”
Section: Methodsmentioning
confidence: 99%
“…Potential risk factors for osteoporosis in this study were classic risk factors for osteoporosis such as age, sex, body weight, malnutrition (assessed using the Patient-Generated Subjective Global Assessment (PG-SGA) malnutrition screening tool recommended by the American Society of Parenteral and Enteral Nutrition (ASPEN)), physical inactivity (assessed using the PG-SGA activities and function evaluation), serum 25-hydroxyvitamin D deficiency, hypocalcemia, hyponatremia, hypogonadism (assessed using serum levels of estradiol, follicle stimulating hormone, luteinizing hormone, and testosterone), hyperparathyroidism, thyroid dysfunction, history of alcohol consumption (yes vs. no; self-reported current or prior alcohol consumption of any frequency or duration), history of cigarette smoking (yes vs. no; self-reported current or prior smoking of any frequency or duration), current use of selective serotonin reuptake inhibitors (SSRIs; yes vs. no), and current use of proton-pump inhibitors (PPIs; yes vs. no) (32-34). …”
Section: Methodsmentioning
confidence: 99%
“…In the case of bone metabolic disorder IBP consumption has been associated with the presence of fractures in young adults 15 , behaving as an independent risk factor for the production of fractures, both as a different studies [3][4][5][6]16 metaanalysis 17 where an increased risk of vertebral, non-vertebral and hip fractures, especially in the elderly was observed. This has caused concern among health authorities who have published several notices on this topic [17][18][19][20] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that consumption of PPIs could be related to an increased risk of fragility fractures. There are published studies in the literature that support this [3][4][5][6] and others that deny it 7 . Moreover, PPIs have been used for many years as a stomach protector that may be caused by taking certain medications.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3][4] Over the last decade, our knowledge of these potential harms has expanded and although some reviewers have concluded that associations may be explained by confounding, 5 other work supports the legitimacy of the earlier safety signals. [6][7][8][9][10] Studies have also emerged more recently reporting other possible serious consequences of PPI use, such as an association with myocardial infarction (MI) and dementia. 11,12 However, further research in these areas is required, to inform our understanding and consequently clarify whether there is a need for us to change PPI prescribing practices.…”
mentioning
confidence: 99%